The influence of changes in brand origin and country of manufacture on willingness to pay for a brand: an experimental study with Brazilian consumers - Montanari, Maria Gabriela (2019)
Despite current criticism on country of origin (COO) as a determinant of consumers\' behavior (COO effect), this cue has regained importance in consumers and marketers\' decisions due to the globalization of business activities. As products are now branded and produced in different countries, COO can be divided into brand origin (BO) - country where a brand is based - and country of manufacture (COM) - country where the brand is produced. Furthermore, both BO and COM are continually changing, as a result of cross-borders acquisitions and production shifts. In these situations, consumers not only have access and evaluate distinct COO information (BO and COM) but also have to deal with a new origin, based on their perceptions about different countries, e.g., country image. Thus, this research examined the relationship between changes in COO (BO and COM) and consumers\' willingness to pay (WTP) for a brand. While is clear by previous literature that there is an interplay between BO and COM, findings are still inconclusive about the most relevant cue to consumers (BO or COM), especially considering acquisitions and production shifts, which can modify consumers\' perceptions of these cues. On the other hand, little is known about how BO and COM can simultaneously influence price outcomes, such as willingness to pay. To achieve the study purpose, an experiment with 413 Brazilian consumers was conducted, involving a specific product category (sunglasses), two countries (USA and China) and three business scenarios: a brand takeover (an alteration in brand origin); an outsourcing (country of manufacture change); and a brand takeover along with an outsourcing (a variation in both brand origin and country of manufacture). First, findings indicated that changes in COO (BO and COM) positively affected consumers\' willingness to pay in the product category of sunglasses. Second, they suggested that both BO and COM exerted an equal effect on consumers\' willingness to pay (WTP), which may be associated with a low brand familiarity or, more likely, with the reduced importance of COO (BO and COM) in the presence of other extrinsic cues, such as the brand, significant in the product category addressed. Finally, asymmetric effects on willingness to pay were revealed, in which consumers paid more for gains than for equivalent losses in BO or/and COM. Therefore, this research contributed to COO studies, drawing insights from signaling theory and prospect theory. It also offered managerial support for pricing decisions and communication strategies: for instance, marketing managers can increase prices when the brand changes to country with a more favorable image, particularly if this new origin reinforces brand associations. In addition, they can communicate BO or COM when these cues carry positive connotations.